Policy Implementation of the Free Nutritious Meal Program Through Collaborative Governance: A Study of the National Nutrition Agency in Kendal Regency - Muhammad Faris Maulana; Rini Werdiningsih; Karmanis Karmanis (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program through a collaborative governance framework in Kendal Regency using a mixed-methods approach with a convergent parallel design. Quantitative data collected from 34 respondents were analyzed using descriptive statistics and Pearson correlation analysis, while qualitative data obtained from five key informants were analyzed thematically. The results reveal very strong and statistically significant correlations (p < 0.001) among cross-sectoral coordination, stakeholder roles, community participation, and accountability–transparency, indicating that collaborative synergy is a decisive factor in successful policy implementation. The Kruskal–Wallis test indicates consensus across professional groups (p> 0.05). However, qualitative findings uncover a paradox of coordination without communication: implementers internalize coordination as a functional operational reality, while beneficiaries experience informational alienation. The resulting collaborative configuration can be characterized as technocratic–instrumentalist—technically effective yet weak in terms of social legitimacy. This study underscores that implementing social policy requires collaborative governance that is not only coordinative but also communicative and deliberative. Policy implications include strengthening dialogic public communication, transforming consultative participation into deliberative engagement, and promoting participatory transparency to foster shared understanding between bureaucratic systems and program beneficiaries.